Absence of RNase H allows replication of pBR322 in Escherichia coli mutants lacking DNA polymerase I. - Kogoma, T (1984)
rnh (formerly termed sdrA) mutants of Escherichia coli K-12, capable of continuous DNA replication in the absence of protein synthesis (stable DNA replication), are devoid of ribonuclease H (RNase H, EC 3.1.26.4) activity. Plasmid pBR322 was found to replicate in rnh mutants in the absence of DNA polymerase I, the polA gene product, which is normally required for replication of this plasmid. The plasmid copy number in polA rnh double mutants was as high as in the wild-type strains. When a chimeric construct between pBR322 and pSC101 was introduced into a polA rnh double mutant, the replication of the plasmid via the pBR322 replicon was inhibited if the plasmid also carried an rnh+ gene or if the host harbored an F' plasmid carrying an rnh+ gene. Thus, DNA polymerase I-independent replication of pBR322 requires the absence of RNase H activity. This alternative mechanism requiring neither DNA polymerase I nor RNase H appears to involve a transcriptional event in the region of the normal origin of replication.